Analyses of Indonesiansâ€™ Engagement with the Anticommunist Master Narrative - Thontowi, Haidar Buldan; Surya, Sofyan Hadi; Rotanza, Yanhizbar; Husainy, Nuhida Kinansa (Psympathic : Jurnal Ilmiah Psikologi, 2024)
Research on narrative engagement centers on personal narratives and how these personal narratives challenge master-narratives. Less attention is paid to narrative engagement in an online context, so the current study aims to explore online narrative engagement of master narratives attached to Indonesiaâ€™s 30 September Movement. We observed online political discourse by retrieving 3,057 tweets using the keyword â€œPKI.â€ We used content analysis to identify relevant themes. Two main themes emerged and represented either support or opposition toward the anti-communist master-narrative. Most tweets in our dataset supported the anti-communist narrative while the remaining were critical of it. We observed that the tweets found predominantly supported anti-communist narratives. Moreover, our research details the unique mechanisms of narrative engagement operative within the online environment. Additionally, we recommend that reconciliation efforts should adopt a subtle approach in challenging the anti-communist narrative to prevent intense opposition.